Natur als Grenzerfahrung Europäische Perspektiven der Mensch-Natur-Beziehung in Mittelalter und Neuzeit: Ressourcennutzung, Entdeckungen, Naturkatastrophen - Kreye, Lars; Stühring, Carsten; Zwingelberg, Tanja (Universitätsverlag Göttingen, 2009)
The book presents the results of a conference at the DFG Graduate College on "Interdiscipline History of Ecology" held in December, 2008. Nature has always been a definite factor for man as well as for societies, and in spite of many attempts to expand his sphere man has had to submit to nature in the face of catastrophies or the limitations of resources. The book comprises scientific and cultural history articles on mediaeval and modern ages, reflecting in a broad spectrum the topic nature as a borderland.